Vitamin D Deficiency and Depressive Symptomatology in Psychiatric Patients Hospitalized with a Current Depressive Episode: A Factor Analytic Study - von Känel, Roland; Fardad, Nasser; Steurer, Nadine; Horak, Nicole; Hindermann, Esther; Fischer, Franz; Gessler, Katharina (PLOS ONE, 2015)
Background Low vitamin D levels have been associated with depressive symptoms in population-based studies and non-clinical samples as well as with clinical depression. This study aimed to examine the association of vitamin D levels with the severity and dimensions of depressive symptoms in hospitalized patients with a current episode of depression taking into account confounding variables. Methods We investigated 380 patients (mean age 47±12 years, 70% women) who were consecutively hospitalized with a main diagnosis of an ICD-10 depressive episode. All patients self-rated depressive symptom severity with the Hospital Anxiety and Depression Scale (HADS-D), the Beck Depression Inventory-II (BDI-II), and the Brief Symptom Inventory. A principal component analysis was performed with all 34 items of these questionnaires and serum levels of 25-hydroxyvitamin D3 (25-OH D) were measured. Results Vitamin D deficiency (<50 nmol/l), insufficiency (50–75 nmol/l), and sufficiency (>75 nmol/l) were present in 55.5%, 31.8% and 12.6%, respectively, of patients. Patients with vitamin D deficiency scored higher on the HADS-D scale and on an anhedonia symptom factor than those with insufficient (p-values ≤0.023) or sufficient (p-values ≤0.008) vitamin D. Vitamin D deficient patients also scored higher on the BDI-II scale than those with sufficient vitamin D (p = 0.007); BDI-II cognitive/affective symptoms, but not somatic/affective symptoms, were higher in patients with vitamin D deficiency (p = 0.005) and insufficiency (p = 0.041) relative to those with sufficient vitamin D. Effect sizes suggested clinically relevant findings. Conclusions Low vitamin D levels are frequent in hospitalized patients with a current episode of depression. Especially 25-OH D levels <50 nmol/l were associated with cognitive/affective depressive symptoms, and anhedonia symptoms in particular.